Deformation of a locally sealed nonlinearly-deformed basis of RPT-pile of minimum materiality under the predetermined load - V. E. Bykhovtsev; V. S. Smorodin; Y. D. Bondareva (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Using the method of numerical and analytical analysis conditions for constructing a RPT-pile of a minimum material capacity for a given load is considered.